Bi-component injection moulding of carbon nanofibre /polypropylene composites for multifunctional parts - Martins, Carla I. (2011)
Polypropylene (PP) is a low cost commodity thermoplastic, easy to process and suitable for general applications. However, for structural and electrical applications, its properties are inadequate, demanding the use of reinforcing materials that may provide mechanical strength and/or electrical conductivity. Carbon-based nanoreinforcements are known for their ability to provide good electrical and mechanical properties to polymer matrix composites. However, the improvement depends essentially on the dispersion and adhesion of the reinforcement in the matrix. In this work PP composites with carbon nanofibres (CNF) were prepared and composite samples were produced; the morphology of the nanocomposite parts was studied and correlated with its mechanical and electrical performance, aiming at understanding the ability of the nanomaterial to be applied in multi-functional parts. The approach followed in this work consisted on the preparation of nanocomposites of PP with varying concentrations of CNF (PP + 2.7 % CNF, PP + 8 % CNF and PP + 4.8% (CNF +CNT)) by blending in a twin-screw extruder. These materials were then processed by co-injection moulding to obtain bi-material parts, producing two types of nanocomposite parts: (i) with an inner core of nanocomposite and an outer layer of PP, and (ii) with an inner core of PP and outer surface layer of nanocomposite. All materials/parts obtained were characterized in terms of their morphological, mechanical, thermal and electrical properties. The morphological results showed a preferential alignment of the nanoreinforcement along the flow direction, and a good dispersion in the polymer matrix; however, CNF adhesion to PP was weak. The mechanical and electrical properties varied with the composition of the bi-material part. Thus, the parts with an inner core of PP presented similar mechanical behavior to PP, with surface antistatic characteristics. The parts with an inner core of CNF nanocomposite presented similar mechanical properties to those of plain CNF nanocomposite parts, presenting semi-conducting characteristics for volume resistivity. It was observed that the incorporation of 1 wt% CNT in a composite with approximately 3% wt CNF lead to similar mechanical and electrical properties to composites with 8% wt CNF content.